(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2022)
ملخص: من أهم أهداف البحث محاولة التعرف على الفرق في مستوى ملكة اللغة العربية، بين تلاميذ السنة الخامسة ابتدائي المداومين على مزاولة حفظ القرآن الكريم وغير المداومين على حفظه. تناول البحث العناصر التالية: -الخطوات الإجرائية للدراسة التطبيقية: تحدث فيه الباحث عن الإجراءات التي اتبعها في العمل التطبيقي. -منهج تحليل أخطاء: وفيه التعريف بمنهج تحليل الأخطاء المتبع في دراسة اللغة المرحلية لمتعلمي اللغة الثانية. -إحصاء الأخطاء النحوية لكلا الفئتين وتصنيفها. -تحليل الأخطاء وتفسيرها: احتوى على مقارنة نتائج الإحصاء بين فئتي التلاميذ وتفسير أسباب الوقوع فيها. الكلمات المفتاحية: الخطأ، التعبير الكتابي، النحو، التلاميذ، القرآن. Abstract: One of its main objectives is to know whether there are differences in the incidence of grammatical error or not. Among the pupils of the fifth year of the primary school those who keep memorizing the Qur’an and not keeping it memorized. the research covered the following elements:-Procedural steps of the applied study: deals with the procedures followed in the applied work.-Method of error analysis: The definition of the method of error analysis used in the study of language errors.- Grammatical errors statistics for both categories and their classification -Analyze and interpret errors:It compares the results of the statistics between the two categories of students and explains their reasons. key words: error, Written expression, Grammar, Disciples, Quran.